Perlindungan Hukum Bagi Pembeli Tanah di Desa Bijaepasu Kabupaten Timor Tengah Utara - Helena Rose T. Banase; Darius Mauritsius; Helsina F. Pello (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2025)
The land sale and purchase agreement with everything above and in it has been implemented and proven by full payment by the buyer so that Article 571 of the Civil Code applies to the buyer. The research method used by the author is Empirical Jurisprudence with a qualitative approach, the data collection for this research is Interview research and Literature Study. the data is then analyzed using qualitative analysis. The results of the study indicate that Legal protection for land buyers in the case of transfer of ownership of teak trees by land sellers to third parties reviewed from the Civil Code guarantees the buyer's rights to the object that has been purchased, namely land and everything attached to the land. based on the Basic Agrarian Law (UUPA) legal protection for land buyers in the case of transfer of ownership of teak trees by land sellers to third parties is very weak. the settlement was carried out through mediation and the seller provided compensation in the form of another teak tree, but this shows that the implementation of the seller's responsibility is not entirely ideal from a formal legal perspective. the seller was proven to have fulfilled the four elements of an unlawful act.